Global Survey of the Frequency of Atrial Fibrillation–Associated Stroke: Embolic Stroke of Undetermined Source Global Registry. Issue 9 (September 2016) - Perera, Kanjana S.; Vanassche, Thomas; Bosch, Jackie; Swaminathan, Balakumar; Mundl, Hardi; Giruparajah, Mohana; Barboza, Miguel A.; O'Donnell, Martin J.; Gomez-Schneider, Maia; Hankey, Graeme J.; Yoon, Byung-Woo; Roxas, Artemio; et al.
Abstract : Background and Purpose—: Atrial fibrillation (AF) is increasingly recognized as the single most important cause of disabling ischemic stroke in the elderly. We undertook an international survey to characterize the frequency of AF-associated stroke, methods of AF detection, and patient features. Methods—: Consecutive patients hospitalized for ischemic stroke in 2013 to 2014 were surveyed from 19 stroke research centers in 19 different countries. Data were analyzed by global regions and World Bank income levels. Results—: Of 2144 patients with ischemic stroke, 590 (28%; 95% confidence interval, 25.6–29.5) had AF-associated stroke, with highest frequencies in North America (35%) and Europe (33%) and lowest in Latin America (17%). Most had a history of AF before stroke (15%) or newly detected AF on electrocardiography (10%); only 2% of patients with ischemic stroke had unsuspected AF detected by poststroke cardiac rhythm monitoring. The mean age and 30-day mortality rate of patients with AF-associated stroke (75 years; SD, 11.5 years; 10%; 95% confidence interval, 7.6–12.6, respectively) were substantially higher than those of patients without AF (64 years; SD, 15.58 years; 4%; 95% confidence interval, 3.3–5.4; P <0.001 for both comparisons). There was a strong positive correlation between the mean age and the frequency of AF ( r =0.76; P =0.0002). Conclusions—: This cross-sectional global sample of patients with recent ischemic stroke shows a substantial frequency of AF-associated stroke throughout the world in proportion to the mean age of the stroke population. Most AF is identified by history or electrocardiography; the yield of conventional short-duration cardiac rhythm monitoring is relatively low. Patients with AF-associated stroke were typically elderly (>75 years old) and more often women.